Surface chemistry considerations of gangue dissolved species in the bastnaesite flotation system - Longhua Xu; Zhoujie Wang; Kaiqian Shu; Houqin Wu; Yuehua Hu (Fundamental Research, 2022)
ABSTRACT: Inefficient flotation of bastnaesite remains a challenge in the production of rare earth elements. This study aimed to investigate the dissolution and adsorption behaviour of species that are commonly released into bastnaesite flotation pulp from Ca/Ba-bearing gangue minerals. The influence and corresponding mechanisms on the bastnaesite mineral surface and collectors, namely sodium oleate (NaOL), were evaluated experimentally based on micro-flotation, zeta potentials, in situ attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR), and X-Ray photoelectron spectroscopy (XPS) analyses. The flotation recovery of bastnaesite significantly decreased from ∼95% to ∼25%, ∼15%, ∼80%, ∼25% when exposed to calcite, fluorite, barite, and mixed dissolved species, respectively. The zeta potential of bastnaesite was pH sensitive, indicating that H+ and OH− determine the surface potential of bastnaesite. Solution chemistry analyses revealed that the presence of the dissolved species differed at various pH values. In situ ATR-FTIR demonstrated the different effects of the dissolved species from calcite, fluorite, and barite on collector adsorption. The former two dissolved species mainly depressed the chemisorption of the NaOL monomers (RCOO‒), whereas calcite also affected the physical adsorption of the oleic acid molecular dimer (RCOOH·RCOO‒). Moreover, the barite dissolved species only affected the physical adsorption of the NaOL species. The results of XPS analysis revealed that dissolved species from these three gangues could pre-adsorbed onto bastnaesite and affected the interaction with the collector. Density functional theory calculations were employed to provide further theoretical insights into the interactions between the dissolved species from calcite, fluorite, and barite and NaOL.